Examining the Relationship Between Sports Participation and Student Motivation: Testing the Mediation of Resilience among University Students in Bahrain - Mohamed Alkashami; Nadeem Khalid; Malak Aoun; Ebtisam Labib; Reem Jasim (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study examines the interplay between sports participation, resilience, and academic motivation among Bahraini university students. Employing a robust theoretical foundation rooted in Self-Determination Theory (SDT), Broaden-and-Build Theory, and the Stress-Buffering Hypothesis, the research explores how sports participation fosters resilience, which in turn mediates its effect on student motivation. Data were collected from 153 university students through validated scales measuring sports participation, resilience, and academic motivation. Structural equation modelling revealed that while sports participation alone did not significantly influence student motivation, its indirect effect through resilience was substantial. The findings underscore resilience as a critical psychological asset that bridges the relationship between sports engagement and academic outcomes. The study highlights the cultural and educational relevance of integrating sports into academic settings to enhance resilience and motivation. Recommendations are provided for policymakers and educators to design resilience-focused interventions leveraging sports participation to optimize academic success. Limitations and directions for future research are also discussed.